Exploitation decision and impact factors in improvement in stock exchange markets proportion investment small (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The purpose of the search definition on factors superior this whoever  impact on the improvement the exploitation  decision this  detect on stock exchange markets  assumption , and using  questioners to data accumulate  and the Iraq market of financial papers  battleground to search annoy chose the eyeball extension (47) peoples from peoples employees on the market , and using the bought statistic program (SPSS) on input and analysis search  data , and machinate the search outputs to their group of factors internal and external which impact on exploitation  decision on financial papers markets , and the search commend on necessary rise  the incumbency direction  in the stock exchange Iraq  markets the give information total that are contingent to help investment on the  exploitation  decision this  detect.